The development of probabilistic thinking among children aged (6-11) years - Khalid Jabbar, Mushtaq (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present research is to identify probabilistic thinking among children ages (6, 7, 8, 9, 10, 11) years, and the significance of statistical differences in probabilistic thinking according to age and gender variables (males and females). The researcher prepared a tool to measure the probabilistic thinking in children after reviewing the previous literature and studies. The tool consisted of (9) paragraphs. On a group of experts, he extracted its psychometric properties, and the research concluded with the following results: T (6) to (11 years) have the ability to probabilistic thinking, the results showed the impact of the age variable in the ability to think about the potential for the benefit of old elder, and the results show the impact of the gender variable in the ability to probabilistic thinking.